Enzyme-Less Growth in Chara and Terrestrial Plants - Boyer, John S. (Frontiers in Plant Science, 2016)
Enzyme-less chemistry appears to control the growth rate of the green alga Chara corallina. The chemistry occurs in the wall where a calcium pectate cycle determines both the rate of wall enlargement and the rate of pectate deposition into the wall. The process is the first to indicate that a wall polymer can control how a plant cell enlarges after exocytosis releases the polymer to the wall. This raises the question of whether other species use a similar mechanism. Chara is one of the closest relatives of the progenitors of terrestrial plants and during the course of evolution, new wall features evolved while pectate remained one of the most conserved components. In addition, charophytes contain auxin which affects Chara in ways resembling its action in terrestrial plants. Therefore, this review considers whether more recently acquired wall features require different mechanisms to explain cell expansion.